Transformation of Malaysian construction industry with Building Information Modelling (BIM) - Latiffi, A. A. (EDP Sciences, 2016)
Building Information Modelling (BIM) is a revolution of technology and a process that transformed the way building is planned, designed, analysed, constructed and managed. The revolution of technology and process could increase the quality of construction projects. The knowledge of BIM has been expanding in many countries including Malaysia. Since its inception, the use of BIM has broadened up widely with different purposes. The aims of this paper is to investigate the BIM implementation and uses in Malaysian construction projects. The methodologies adopted for structuring this paper are by using literature review and semi-structured interview with construction players that have experienced and being involved in projects using BIM. The purpose of literature review is to illustrate on the pervious research on the subject matter. Meanwhile, the purpose of interviews is to explore the involvement of construction players, years of experience in projects using BIM and BIM uses in construction projects. The findings revealed that BIM has been implemented in Malaysia since 2007 by various construction players, which are client, architect, C&S engineer, M&E engineer, QS, contractor, facilities manager and BIM consultant. The findings also revealed that BIM is used for project' visualisation, improving project design, detecting design clashes, quantity take off and operation and maintenance. Further work will be focused on the current practices of construction players in projects using BIM.